THE USE OF THE WEIGHTED PRODUCT (WP) METHOD IN ASSESSING THE PERFORMANCE OF DOCTORS AT SETIO HUSODO HOSPITAL - Dwi arisca Pratiwi; Hambali Hambali; Zulfan Efendi (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2023)
In a hospital, the doctor's role is very important. A doctor is someone who because of his knowledge tries to heal the sick. Doctors must have professionalism and quality in providing quality health services. One of the efforts to spur the performance of doctors is to conduct performance evaluations in order to increase the spirit of performance and achievement. Currently the job evaluation system at Setio Husodo Hospital is still done conventionally and the results of the assessment are subjective. By using a computer as a tool in the decision-making process for assessing the performance of doctors supported by the weighted product (WP) method to obtain accurate results. This study aims to design a Decision Support System application for assessing the performance of doctors which later deserves to be rewarded by Setio Husodo Hospital by looking at the value of the criterion weights and then processing the ratings of the doctor's performance assessment. The results of the study are in the form of an application that can show the value and ranking of the credibility of a doctor at Rs. Setio Husodo.